Effect of Ultradisperse TiO2, ZrO2, and Cryolite Powders on High-Chromium Cast Iron Hardening - Zykova A. P. Anna Petrovna; Popova N. A. Nataljya Anatoljevna; Nikonenko E. L. Elena Leonidovna; Kurzina I. A. Irina Aleksandrovna (2016, 2016)
Title screen